An Analysis of Wideband Phased Array Antenna System using with Micro strip Filter (International Journal of Engineering and Computer Science, 2014)
Wideband phased array antenna system designed for multi-channel and multi-function process. Wideband phased array antennas consist of multiple fixed antenna elements, which can be energized in a different way and in order to manage the radiation pattern. The phased array antenna system is designed to work from 3 to 12 GHz. So each element is designed to work within the above bandwidth. Antenna elements are other important components of a phased array antenna. The dielectric substrate changes the effective dielectric constant of the micro strip line, and cause different phase shifts on the micro strip line.